CFD modelling of wind flow over terrain - Stangroom, Paul (2004)
The aim of this project is to show the capabilities of a RANS based numerical model in accurately analysing wind flow over real terrain regions, and assess its usage for wind energy applications. The main reasons this type of model is not widely used in the wind energy industry are due to the computational cost and the expertise required to operate such a model. These factors are assessed and various setups of the model are examined to consider the accuracy attained. The modelling process is also automated to reduce necessary user input in the process.